2018
DOI: 10.1111/1556-4029.13756
|View full text |Cite
|
Sign up to set email alerts
|

Distinction of Fly Artifacts from Human Blood using Immunodetection

Abstract: Insect stains produced by necrophagous flies are indistinguishable morphologically from human bloodstains. At present, no diagnostic tests exist to overcome this deficiency. As the first step toward developing a chemical test to recognize fly artifacts, polyclonal antisera were generated in rats against three distinct antigenic sequences of fly cathepsin D‐like proteinase, an enzyme that is structurally distinct in cyclorrhaphous Diptera from other animals. The resulting rat antisera bound to artifacts produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…Since Rivers et al [10][11][12] has reported that only artifacts derived from alimentary canal of the adult flies reacted positively to the immunoassay test, we have chosen to analyze fly artifacts more likely originated from regurgitation or fecal elimination processes, excluding transfer pattern stains produced by tarsi or other body parts, because fly touch DNA was not expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Rivers et al [10][11][12] has reported that only artifacts derived from alimentary canal of the adult flies reacted positively to the immunoassay test, we have chosen to analyze fly artifacts more likely originated from regurgitation or fecal elimination processes, excluding transfer pattern stains produced by tarsi or other body parts, because fly touch DNA was not expected.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, Rivers et al [10,11] tested a polyclonal antiserum (anti-md3 serum) generated toward a unique cathepsin D proteinase that has been shown to react with regurgitate and defecatory fly artifacts produced by different species of blowflies, but not with transfer patterns or blood controls from humans or other animals. Recently, the study was extended to other stains produced by different species of flies following the consumption of semen, saliva, feces, and urine, showing that more than 94% of fly artifacts reacted positively with anti-md3 [12].…”
Section: Introductionmentioning
confidence: 99%
“…A sizable amount of work has been done on fly artifacts, including various detection techniques (Rivers et al, 2018; Rivers et al, 2019; Rivers, Cavanagh, Greisman, Brogan, & Schoeffield, 2020) and analyses of their stains (Rivers, Dunphy, Hammerschmidt, & Carrigan, 2020; Rivers & Geiman, 2017; Rivers & McGregor, 2018). Other work relating to entomotoxicology found that both opiates (Introna, Dico, Caplan, & Smialek, 1990) and barbiturates (Levine, Golle, & Smialek, 2000) could be obtained from larvae feeding on remains that had ingested these drugs.…”
Section: Forensic Entomological Literature In the Northeastmentioning
confidence: 99%
“…The authors report that the antiserum is able to detect the synthetic peptide created for the development of the assay to a dilution of 1:500,000. While the occasional false negative has occurred, the test shows real promise (Rivers et al, ; D. B. Rivers et al, 2019). Strong positive reactions have been obtained from artifacts stored for 3, 5, and 7 years at 25°C.…”
Section: Retrieval Of Extraneous Dna From Insectsmentioning
confidence: 99%
“…Strong positive reactions have been obtained from artifacts stored for 3, 5, and 7 years at 25°C. However, the group is yet to test whether chemical alteration of the artifacts through application of cleaning products or extended exposure to environmental conditions such as ultraviolet light, might impact on the efficacy of the test, and whether the antisera would be effective on fly artifacts deposited after feeding on human biological material other than blood, or artifacts deposited in the field (Rivers et al, ; D. B. Rivers et al, 2019).…”
Section: Retrieval Of Extraneous Dna From Insectsmentioning
confidence: 99%